The models of work in approaches to livestock farming systems - Dedieu B.; Serviere G. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
In France, several work models, which underlie research and tools for work advice, coexist in approaches to analyse how livestock farming systems (LFS) function. We describe three models: resource work, organised work, work and subjectivity and specify the way in which LFS research has mobilised social science disciplines to construct them. We illustrate how they complement each other to examine the transformations in livestock farming systems, the ways in which the farming activity is carried out, the conceptions of work, as well as the workforce and technical systems.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)